METHODICAL ASPECTS OF USING VIRTUAL MUSEUMS OF THE EDUCATIONAL PROCESS IN GENERAL EDUCATION INSTITUTIONS - Soroko , Nataliia (Physical and Mathematical Education, 2022)
The large-scale pandemic caused by Covid-19 forced long vacations and the unstable situation in the country has raised one of the global problems of education - quality educational content.Formulation of the problem. World culture of the XXI century exists in a dynamic environment that is rapidly evolving in all areas of human activity. Information and communication technologies have a significant impact on socio-cultural processes. At the same time, the concept of «virtuality» is firmly in the context of culture, education, and business. One of the important innovations that have taken a significant place in cultural life is a phenomenon such as a virtual museum.Materials and methods. We used the following methods to achieve the goal of the study: systematic and comparative analysis of pedagogical, psychological, philosophical, sociological works, methodological and specialized literature; analysis of the pedagogical experience of using virtual museums of the education in general secondary education institutions; questioning teachers about their experience of using virtual museum in the educational process, identifying problems for the creation of special webinars and courses to develop digital competence of teacher; interpretation of research results.Results. The use of virtual museums in the educational process makes it possible to effectively solve the following basic didactic tasks: ensuring the scientific nature for students'education mastery of scientific knowledge and promoting the formation of a democratic worldview in them that based on credible scientific facts and corresponds to the dynamics of of relevant scientific knowledge development; strengthening the clarity of learning as a principle of didactics, due to the nature of the process of cognition, which begins with sensory perception, moves to abstract thinking, and from it to practice; development of student’s cognitive interests and abilities as a principle of didactics, which determines the most important motives for student learning (formation of cognitive interests occurs through two ways: through the material that constitutes the content of learning and organization of students cognitive activity); the use of virtual museums can affect students' visual and auditory memory; accelerating the pace of learning and memorizing learning material, which contributes to the strength of knowledge, expanding the cognitive interests of students; the intensification of students' independent work; the connection between theory and practice, which necessitates the reflection of two inextricably linked aspects of a single education process; individualization of learning.Conclusions. The virtual museum makes it possible to significantly supplement, expand, and deepen the content of the material studied in the curriculum. Using virtual museums, the teacher can best select educational material. Virtual museums allow in the simplest, most intelligible, and emotional way to transfer educational material, significantly enhance the mental activity of students, expand their worldview, and arouse special interest in a particular field of knowledge. For the use of virtual museums in the educational process to promote the development and formation of cognitive interests of students, the teacher must: select information to be presented with the help of virtual museum, by content and compose it in a composition so that it corresponds to the purpose, age, knowledge, and interests  of  students;  the  use  heuristic  methods  in  teaching  educational material with the help of virtual museum; to organize by the specific interests of students various forms of independent work with the use of virtual museum (preferably in the form of educational projects).
Keywords: virtual reality; virtual museum; secondary school; quality of educational content; methodical aspects